Composite particle of seed particle and cobalt ferrite particle and manufacturing method thereof

JP2025042610APending Publication Date: 2025-03-27NITTETABU MINING CORP
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2024158125
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-09-14
Filing Date
2024-09-12
Publication Date
2025-03-27

Smart Images

  • Figure 2025042610000001_ABST
    Figure 2025042610000001_ABST
Patent Text Reader

Abstract

To provide a manufacturing method capable of synthesizing a composite particle of a seed particle and a cobalt ferrite particle having a particle diameter in the specified range, with a roundish shape having a predetermined average circularity, and having specified magnetic properties with lower energy, and a composite particle of a seed particle and a cobalt ferrite particle manufactured thereof, with a roundish shape having a predetermined average circularity, having specified magnetic properties, and having uniform particle diameter.SOLUTION: A manufacturing method of composite particle of a seed particle and a cobalt ferrite particle includes steps of: preparing a ferrite precursor by stabilization of a bivalent iron salt and a cobalt salt in an aqueous solution by using a complexing agent; adding a spherical or approximately spherical seed particle to the ferrite precursor; and further heating the ferrite precursor.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a composite particle of seed particles and cobalt ferrite particles, and a method for producing the same. The present invention provides a composite particle of seed particles and cobalt ferrite particles, which has a particle diameter within a specific range, a rounded shape with a predetermined average circularity, and specific magnetic properties. [Background technology]

[0002] Ferrite particles are known as a high magnetic permeability material and a permanent magnet material, and today magnetic powders are being used in new materials such as copy toner, magnetic ink, and MR fluids, and there are high expectations for improvements in their quality and performance. Cobalt ferrite, in particular, is known as a magnetic material with large crystal magnetic anisotropy and large coercive force among spinel ferrites. In addition, cobalt has a chemical behavior similar to that of iron, which makes it easy to control various aspects of the manufacturing process.

[0003] Known methods for producing ferrite particles include a coprecipitation method, a wet oxidation method, and a hydrothermal method. The coprecipitation method is a reaction in which two or more types of ions are precipitated at the same time. In the case of producing cobalt ferrite particles, Fe 3+ and C 2+ After adding an alkali to an aqueous solution containing ions, the reaction is accelerated by heating to obtain nano-sized ferrite particles. In this method, the reaction is carried out at a temperature of 80 to 100°C, and the average particle size of the obtained particles is about 20 to 50 nm, and only particles with a relatively wide particle size distribution are obtained (Patent Document 1).

[0004] The wet oxidation method is 2+ and C 2+This method involves reacting an oxidizing agent such as air with a raw aqueous solution containing ions while heating it. When air is used as the oxidizing agent, the reaction temperature is about 60 to 100°C, and particles of about 0.05 to 0.3 μm are obtained (Patent Document 2, Patent Document 3). In addition, in a method in which the raw aqueous solution and the oxidizing agent liquid are reacted continuously, the reaction is carried out at a temperature of 30 to 100°C, and ferrite particles of 3 to 20 nm are obtained (Patent Document 4).

[0005] The hydrothermal method is 2+ In an aqueous solution containing ions, 2+ Ferrite particles having a relatively large particle size of 0.3 to 8 μm are produced by mixing an aqueous solution containing ions and carrying out hydrothermal synthesis in an autoclave at a high temperature of 160 to 300° C. (Patent Document 5).

[0006] When ferrite particles are produced by conventional techniques, the coprecipitation method or wet oxidation method can produce them at a relatively low temperature, but the obtained ferrite particles are only fine particles on the order of nm. In addition, the hydrothermal method can produce relatively large particles on the order of μm, but it requires a hydrothermal reaction (siccol reaction) at high temperature and pressure, which creates problems in terms of equipment and cost. [Prior art documents] [Patent documents]

[0007] [Patent Document 1] Patent No. 4138344 [Patent Document 2] Special Publication No. 3-24412 [Patent Document 3] Special Publication No. 60-47722 [Patent Document 4] Patent No. 5504399 [Patent Document 5] Japanese Patent Application Publication No. 5-275224 Summary of the Invention [Problem to be solved by the invention]

[0008] In the conventional manufacturing process of cobalt ferrite particles, when the particle diameter was reduced, the particles lost their roundness and became irregular in shape. When using cobalt ferrite particles in copy toner, magnetic ink, and MR fluid, if the particle surfaces are rounded, the particle surfaces can be uniformly coated with the minimum amount of surface treatment agent required. However, if the particle surfaces are irregular, the amount of surface treatment agent used increases, resulting in extra costs. The average circularity of particles is considered to be one of the scales for evaluating the degree of roundness of the particle surface. Therefore, there has been a demand for cobalt ferrite particles or composite particles containing cobalt ferrite that have a predetermined average circularity and rounded particle surfaces and can be uniformly coated with a minimum necessary amount of a surface treatment agent. As described above, the present invention overcomes the problems of the conventional technology and provides a production method capable of synthesizing composite particles of seed particles and cobalt ferrite particles with lower energy, the particle size of which is within a specific range, the shape of which has a predetermined average circularity and which has specific magnetic properties. The present invention also provides composite particles of seed particles and cobalt ferrite particles, the particle size of which is within a specific range, the shape of which has a predetermined average circularity and which has specific magnetic properties, produced by the above production method. [Means for solving the problem]

[0009] In order to solve the above problems, the present invention employs the following means. (1) A method for producing composite particles of seed particles and cobalt ferrite particles, comprising the steps of: preparing a ferrite precursor by stabilizing a divalent iron salt and a cobalt salt in an aqueous solution with a complexing agent; adding spherical or nearly spherical seed particles to the ferrite precursor; and further heat-treating the ferrite precursor. (2) The method for producing composite particles of seed particles and cobalt ferrite particles according to (1), wherein the heat treatment is carried out in a pressure vessel under hydrothermal conditions in a temperature range of 130°C to 260°C. (3) The method for producing composite particles of seed particles and cobalt ferrite particles according to (2), wherein the heat treatment is carried out in a pressure vessel under hydrothermal conditions in a temperature range of 190°C to 240°C. (4) The method for producing composite particles of seed particles and cobalt ferrite particles according to (2) or (3), wherein the time for the heat treatment step is 1 to 50 hours. (5) A method for producing composite particles of seed particles and cobalt ferrite particles according to (3), wherein the heat treatment is carried out under hydrothermal conditions by heating to a temperature range of 190°C to 210°C, holding the first reached temperature, and further heating to a temperature range of 210°C to 240°C, and holding the second reached temperature. (6) A method for producing composite particles of seed particles and cobalt ferrite particles according to any one of (1) to (5), comprising maintaining the first attained temperature for 1 to 14 hours. (7) The method for producing composite particles of seed particles and cobalt ferrite particles according to any one of (1) to (6), wherein the second attainment temperature is maintained for 0.5 to 12 hours. (8) The method for producing composite particles of seed particles and cobalt ferrite particles according to any one of (1) to (7), wherein the seed particles are at least one selected from iron, an iron-based alloy, iron oxide, spinel ferrite, and silica. (9) The method for producing composite particles of seed particles and cobalt ferrite particles according to any one of (1) to (8), wherein the divalent iron salt and the cobalt salt are iron(II) sulfate and cobalt(II) sulfate. (10) The method for producing composite particles of seed particles and cobalt ferrite particles according to any one of (1) to (8), wherein the divalent iron salt and the cobalt salt are iron(II) chloride and cobalt(II) chloride. (11) The method for producing composite particles of seed particles and cobalt ferrite particles according to any one of (1) to (10), wherein the complexing agent is one selected from the group consisting of citrate, nitrilotriacetate, and malate. (12) The method for producing composite particles of seed particles and cobalt ferrite particles according to any one of (1) to (11), wherein the heat treatment step is carried out in the presence of an oxidizing agent in addition to a complexing agent. (13) The method for producing composite particles of seed particles and cobalt ferrite particles according to (12), wherein the oxidizing agent is a nitrate. (14) The method for producing composite particles of seed particles and cobalt ferrite particles according to any one of (1) to (13), further comprising adding a trivalent iron salt to the aqueous solution containing the ferrite precursor. (15) The method for producing composite particles of seed particles and cobalt ferrite particles according to any one of (1) to (14), further comprising adding a pH buffer to the aqueous solution containing the ferrite precursor. (16) A method for producing composite particles of seed particles and cobalt ferrite particles according to any one of (1) to (15), comprising: injecting an alkaline aqueous solution or a ferrite precursor into a pressure vessel during or after a heat treatment step; and further carrying out a heat treatment. (17) Composite particles of seed particles and cobalt ferrite particles, which have a rounded shape with an average circularity of 0.7 to 1.0, a particle diameter corresponding to a cumulative value of 50% based on a particle size distribution of 1 to 30 μm, and a particle diameter corresponding to a cumulative value of 95% based on a particle size distribution of 5 to 50 μm. (18) Composite particles of seed particles and cobalt ferrite particles according to (17), having a remanent magnetic moment of 10 emu / g or more and a coercive force of 100 to 1000 Oe. (19) A toner for copying comprising composite particles of the seed particles according to (18) and cobalt ferrite particles. (20) A magnetic ink comprising composite particles of the seed particles according to (18) and cobalt ferrite particles. (21) An MR fluid comprising composite particles of the seed particles according to (18) and cobalt ferrite particles. (22) A white powder comprising a composite particle of the seed particle and cobalt ferrite particle according to (18) above, and having a titanium oxide film and a metallic silver film on the surface of the composite particle in this order. (23) The white powder according to (22), having a lightness L* of 75 or more. Effect of the Invention

[0010] By employing the manufacturing method of the present invention, it is possible to produce magnetic particles consisting of composite particles of seed particles and cobalt ferrite particles, which have a particle diameter within a specific range, a rounded shape with a prescribed average circularity, and specific magnetic properties, with lower energy than magnetic particles produced by conventional methods. The composite particles of the seed particles and the cobalt ferrite particles obtained by the production method of the present invention have a rounded shape and a uniform particle size, and are therefore expected to be used as copy toners, magnetic inks, MR fluids, etc. The composite particles of the seed particles and the cobalt ferrite particles of the present invention can be whitened by a known method, or can be further provided with a colored layer to form a white powder with high brightness or a colored powder colored in a vivid color. [Brief description of the drawings]

[0011] [Figure 1] Fig. 1A is an SEM photograph of the composite particles of Example 1. Fig. 1B is an SEM photograph of iron (Fe) used as seed particles in Example 1. [Diagram 2] 2A is a SEM photograph of the composite particles of Example 2. FIG. 2B is a SEM photograph of iron (Fe) used as seed particles in Example 2. [Diagram 3] 3A is a SEM photograph of the composite particles of Example 3. FIG. 3B is a SEM photograph of iron (Fe) used as seed particles in Example 3. [Figure 4] Fig. 4A is an SEM photograph of the composite particles of Example 4. Fig. 4B is an SEM photograph of iron (Fe) used as seed particles in Example 4. [Diagram 5] Fig. 5A is a SEM photograph of the composite particles of Example 5. Fig. 5B is a SEM photograph of iron (Fe) used as seed particles in Example 5. [Figure 6] Fig. 6A is an SEM photograph of the composite particles of Example 6. Fig. 6B is an SEM photograph of zinc ferrite, a type of spinel ferrite, used as seed particles in Example 6. [Figure 7]Fig. 7A is an SEM photograph of the composite particles of Example 7. Fig. 7B is an SEM photograph of Alnico, a type of iron-based alloy used as seed particles in Example 7. [Figure 8] Fig. 8A is an SEM photograph of the composite particles of Example 8. Fig. 8B is an SEM photograph of magnetite, a type of iron oxide, used as seed particles in Example 8. [Figure 9] 9A is a SEM photograph of the composite particles of Example 9. FIG. 9B is a SEM photograph of the silica used as seed particles of Example 9. [Figure 10] 10A is a SEM photograph of the composite particles of Example 10. FIG. 10B is a SEM photograph of iron (Fe) used as seed particles of Example 10. [Figure 11] Fig. 11A is an SEM photograph of the composite particles of Reference Example 1. Fig. 11B is an SEM photograph of iron (Fe) used as seed particles of Reference Example 1. [Figure 12] Fig. 12A is an SEM photograph of the composite particles of Reference Example 2. Fig. 12B is an SEM photograph of iron (Fe) used as seed particles of Reference Example 2. [Figure 13] Fig. 13A is an SEM photograph of the composite particles of Comparative Example 1. Fig. 13B is an SEM photograph of the non-spherical magnetite used as seed particles of Comparative Example 1. [Figure 14] Fig. 14A is an SEM photograph of the composite particles of Comparative Example 2. Fig. 14B is an SEM photograph of the non-spherical magnetite used as seed particles in Comparative Example 2. [Figure 15] Fig. 15A is an SEM photograph of the composite particles of Comparative Example 3. The white frame in Fig. 15A indicates impurities. Fig. 15 is an SEM photograph of iron (Fe) used as seed particles in Comparative Example 3. [Figure 16] 16A and 16B are schematic cross-sectional diagrams, based on TEM observation, of the composite particle of Example 1. In this specification, a scanning electron microscope may be abbreviated as "SEM" and a transmission electron microscope as "TEM". DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012] [Method for producing composite particles of seed particles and cobalt ferrite particles] A method for producing a composite particle of a seed particle and a cobalt ferrite particle (hereinafter, also simply referred to as a "composite particle") according to an embodiment includes the steps of: (a) preparing a ferrite precursor by stabilizing a divalent iron salt and a cobalt salt in an aqueous solution with a complexing agent; (b) adding spherical or nearly spherical seed particles to the ferrite precursor; (C) further comprising a step of heat treating the ferrite precursor. The method for producing the composite particles will be described below step by step.

[0013] (A) (Ferrite precursor preparation process) First, a complexing agent is dissolved in demineralized water. This is because the ferrite precursor can be protected from oxidation by an oxidizing agent by complexing it with a complexing agent before heat treatment. The complexing agent is not particularly limited, and citrate, nitrilotriacetate, malate, and the like are preferred. When a citrate is used, composite particles of seed particles and cobalt ferrite particles with a large particle size of about 1 to 30 μm are obtained. When a nitrilotriacetate or malate is used, fine particles with an average particle size of 1 μm or less are obtained. Next, a cobalt salt is dissolved in the aqueous solution. The cobalt salt is not particularly limited, and examples thereof include divalent cobalt salts such as cobalt(II) sulfate, cobalt(II) chloride, cobalt(II) nitrate, and cobalt(II) acetate. In view of availability, cobalt(II) sulfate or cobalt(II) chloride is preferred. In this case, an oxidizing agent may be added. The oxidizing agent is not particularly limited, and examples thereof include nitrates, hypochlorites, chlorates, perchlorates, permanganates, dichromates, chromates, manganates, peroxides, etc. From the viewpoint of improving stability, nitrates are preferred. The aqueous solution containing the cobalt salt is then degassed by applying an inert gas to reduce the dissolved oxygen concentration. The reason for degassing is to prevent the charge state of metal ions such as iron dissolved in the aqueous solution in the subsequent process from being affected by the dissolved oxygen. For example, it is known that the presence of free oxygen in the reaction system oxidizes divalent iron to trivalent iron, resulting in the generation of particles or impurities with undesired properties.

[0014] Next, a divalent iron salt is dissolved in the degassed aqueous solution to prepare a raw material aqueous solution. The divalent iron salt is not particularly limited, and examples thereof include iron sulfate (II), iron chloride (II), iron nitrate (II), and iron acetate (II). Iron washing wastewater from blast furnaces and electric furnaces can also be used as an inexpensive raw material. In view of ease of availability, iron sulfate (II) or iron chloride (II) is preferred. As will be described later in the section on adjusting the particle size, a trivalent iron salt may be further added to the aqueous solution. The trivalent iron salt is not particularly limited, and examples thereof include iron chloride (III), iron sulfate (III), and iron nitrate (III).

[0015] Examples of the combination of the divalent iron salt and the cobalt salt include iron(II) sulfate and cobalt(II) sulfate, or iron(II) chloride and cobalt(II) chloride.

[0016] Then, an alkali is dissolved in demineralized water to prepare an alkaline aqueous solution. The alkali may be any alkali such as sodium hydroxide, potassium hydroxide, calcium hydroxide, ammonia, etc. An aqueous solution of an alkali that is dissolved in the water may be prepared from the beginning. Furthermore, an alkaline aqueous solution is added to the raw material aqueous solution to adjust the pH, thereby preparing a ferrite precursor. In order to stably form the complex, it is preferable to dissolve and mix the raw materials in the above order. In addition, in order to synthesize ferrite particles having good properties after the complex is decomposed, it is preferable to adjust the pH after adding the alkaline aqueous solution to about 6 to 13.

[0017] (B) (Seed particle addition process) Seed particles are added to the ferrite precursor. By adding the seed particles to the ferrite precursor, nuclei that serve as substrates for precipitating cobalt ferrite particles can be provided, and the particle size of composite particles of the seed particles and the cobalt ferrite particles can be adjusted. The seed particles used here are not particularly limited and are selected from water-insoluble inorganic compounds such as metals, alloys, and oxides. In particular, in view of their affinity with cobalt ferrite, iron, iron-based alloys, iron oxide, spinel ferrite, and silica are preferred as seed particles. As iron oxide, magnetite, hematite, goethite, and lepidocrocite can be used. In addition, by using spherical or nearly spherical seed particles, the shape of the composite particles of the seed particles and cobalt ferrite particles to be synthesized can be made closer to a sphere.

[0018] In this specification and claims, "spherical" refers to a shape similar to a sphere. "Nearly spherical" includes shapes close to a sphere and polyhedrons consisting of multiple faces. In addition, in this specification and claims, anything that is not "spherical" or "nearly spherical" is referred to as "non-spherical." Examples of "non-spherical" shapes include cubes and rectangular parallelepipeds.

[0019] The particle diameter of the seed particles is 0.1 μm to 50 μm, preferably 0.5 μm to 30 μm, and more preferably 1 μm to 20 μm. The particle diameter of the seed particles can be measured by a laser diffraction / scattering method.

[0020] (C) (Heat treatment process) Heat treatment is carried out by a hydrothermal method using a pressure vessel. The pressure vessel may be a normal high-pressure reaction vessel, such as an autoclave, a pressure cooker, or a boiler, but an autoclave is preferred for its versatility. In a typical high-temperature siccol method, the reaction often proceeds at a high temperature of 200°C or higher. In this embodiment, however, by selecting a complexing agent, magnetic particles consisting of composite particles of seed particles and cobalt ferrite particles can be synthesized at a temperature range of about 130 to 300°C, preferably about 130 to 280°C, more preferably about 130 to 260°C, and even more preferably about 130 to 240°C.

[0021] From the viewpoint of expecting a high reaction rate, the heat treatment temperature is preferably higher than 190° C. and equal to or lower than 300° C. On the other hand, impurities tend to be introduced when the reaction temperature exceeds about 270° C. For this reason, from the viewpoint of achieving a balance between purity and reaction rate, the reaction temperature is preferably 190 to 270° C., more preferably 190 to 260° C., even more preferably 190 to 240° C., and even more preferably 195 to 240° C. The heat treatment time is preferably from 1 to 50 hours, more preferably from 1 to 45 hours, and further preferably from 1 to 40 hours.

[0022] The temperature of the heat treatment does not need to be constant, and it may be performed at different temperatures in multiple stages. For example, it is preferable to heat to a temperature range of 190 to 210°C in the first stage and hold the first reached temperature. It is preferable to hold the first reached temperature for 1 to 14 hours, more preferably for 1 to 12 hours, and even more preferably for 4 to 12 hours. Furthermore, in the second stage, the heat treatment can be performed by heating to a temperature range of 210 to 240° C., preferably to a temperature range of 220 to 240° C., and then holding the second reached temperature. The second reached temperature is preferably held for 0.5 to 12 hours, more preferably for 0.5 to 10 hours, and even more preferably for 0.5 to 2 hours.

[0023] When heat treatment is performed at different temperatures in multiple stages, the relatively low temperature stage suppresses excessive progress of the oxidation reaction of the ferrite precursor, thereby suppressing excessive aggregation between the seed particles and contributing to making the composite particles of the seed particles and the cobalt ferrite particles closer to a spherical shape. The relatively high temperature stage promotes the oxidation reaction of the ferrite precursor, thereby contributing to improving the magnetic properties, improving the yield, and adjusting the particle size. In addition, by performing heat treatment in multiple stages, the total heat treatment time can be shortened.

[0024] (Role of complexing agent) The complexing agent plays an important role in the ferrite synthesis reaction, which is believed to proceed as follows. Before the hydrothermal treatment, the oxidizing reaction by the oxidizing agent does not occur, and the ferrite precursor is stable in the aqueous solution due to the complexing action of the ligands of the complexing agent. This prevents the generation of hydroxides, which are easily oxidized and unstable, and the precursor is stably protected. Next, when heating is started, the complexing agent that protected the metal ions gradually decomposes, and the metal ions become susceptible to oxidation. At this time, an oxidizing agent such as sodium nitrate may be added to uniformly promote the oxidation reaction for forming ferrite. If the ferrite precursor is in an oxidizing environment, it is oxidized by the oxidizing agent, and even if there is no oxidizing agent, it is oxidized by the action of the hydrothermal environment to form ferrite.

[0025] The complexing action of the complexing agent can delay the progress of the oxidation reaction of the ferrite precursor during heat treatment under hydrothermal conditions. This allows the particle size of the synthesized ferrite particles to be increased, and particles with a uniform particle size can be produced. In addition, by controlling the progress of the oxidation reaction of the ferrite precursor, excessive aggregation of the seed particles can be suppressed, and as a result, composite particles of seed particles and cobalt ferrite particles with a shape close to spherical can be produced.

[0026] (Particle size adjustment 1: Addition of trivalent iron salt) In the method for producing a composite particle of seed particles and cobalt ferrite particles according to the present embodiment, a means for adjusting the particle size of the composite particle of seed particles and cobalt ferrite particles to be produced can be adopted in each step of the production method. Some particle size adjustment means are listed below. These means can be adopted alone or in combination of a plurality of means. By adding a trivalent iron salt to the raw material aqueous solution (an aqueous solution of a divalent iron salt and a cobalt salt), the particle size of the composite particles of the seed particles and the cobalt ferrite particles can be adjusted by adding a trivalent iron salt to the aqueous solution containing the divalent iron salt and the cobalt salt stabilized with a complexing agent. In this way, the trivalent iron ions of the trivalent iron salt act as nuclei for the formation of ferrite particles, so that the reaction of ferrite formation is promoted regardless of the presence or absence of an oxidizing agent, and the particle size of the composite particles of the seed particles and the ferrite particles to be produced can be adjusted. The iron(III) salt used here is not particularly limited, and examples thereof include iron chloride (III), iron sulfate (III), and iron nitrate (III). Iron washing wastewater from blast furnaces and electric furnaces may also be used as an inexpensive raw material.

[0027] (Particle size adjustment 2: Addition of pH buffer) By adding a pH buffer to an alkaline aqueous solution (aqueous solution of an alkali and a complexing agent), the particle size of the composite particles of seed particles and cobalt ferrite particles can be adjusted by adding a pH buffer to an aqueous solution containing a divalent iron salt and a cobalt salt stabilized by a complexing agent. The ferrite formation reaction is accompanied by a decrease in pH, and a decrease in pH suppresses the decomposition of the ferrite precursor and inhibits the ferrite formation reaction. Therefore, by adding a pH buffer to suppress the decrease in pH, the growth of ferrite particles can be promoted. The pH buffer used here is selected from boric acid, sodium carbonate, sodium bicarbonate, and the like.

[0028] (Particle size adjustment 3: Injection of alkaline aqueous solution and ferrite precursor during heat treatment) During or after the heat treatment step, an alkaline aqueous solution or a ferrite precursor (complex) is injected into the pressure vessel, and the heat treatment is continued thereafter, thereby making it possible to adjust the particle size of the composite particles of the seed particles and the cobalt ferrite particles. When the alkaline aqueous solution is injected, the pH in the reaction vessel rises, which accelerates the decomposition of unreacted ferrite precursors and promotes the ferrite formation reaction. This allows for particle growth (coarsening). The alkaline aqueous solution is not particularly limited and can be appropriately selected from sodium hydroxide, potassium hydroxide, calcium hydroxide, ammonia, etc. On the other hand, when the ferrite precursor (complex) is injected, the ferrite forming raw material is added, and the particle growth of the ferrite particles can be promoted. The method for producing the ferrite precursor is as described above.

[0029] [Composite particles of seed particles and cobalt ferrite particles] As an index of particle size of the composite particles of seed particles and cobalt ferrite particles, a particle size corresponding to 50% or 95% of the cumulative value based on the particle size distribution can be used. The particle size distribution of the composite particles can be measured, for example, by a laser diffraction / scattering type particle size distribution measuring device (manufactured by Microtrack Bell, model number "MT3300EXII"). The specific particle size distribution is as follows. The composite particles of seed particles and cobalt ferrite particles have a particle size corresponding to 50% of the cumulative value based on the particle size distribution in the range of 1 to 30 μm, and a particle size corresponding to 95% of the cumulative value based on the particle size distribution in the range of 5 to 50 μm. The composite particles of the seed particles and the cobalt ferrite particles have magnetic properties of an average circularity in the range of 0.7 to 1.0, more preferably 0.70 to 0.95, a remanent magnetic moment of 10 emu / g or more, and a coercive force of 100 to 1000 Oe. The composite particles of the seed particles and the cobalt ferrite particles have a rounded shape and a uniform particle size. The aspect ratio of the composite particles is approximately 1. 16A and 16B, one embodiment of the composite particle of seed particles and cobalt ferrite particles is a core-shell type composite particle having a single seed particle as shown in Fig. 16A, and islands-in-the-sea type composite particles B-1 to B-4 having a plurality of seed particles as shown in Fig. 16B. The number of seed particles is not limited, but may be 2 to 15, for example. The composite particles of the seed particles and the cobalt ferrite particles of this embodiment have a relatively large particle size, are rounded, and have a narrow particle size distribution, so that they have little cohesion between particles and can be closely packed when molded, which improves the magnetic properties of the molded body or increases the bulk density. In addition, the composite particles of the seed particles and the cobalt ferrite particles of this embodiment have a rounded shape, so that the amount of surface treatment agent used can be reduced when treating the surface of the composite particles of the seed particles and the cobalt ferrite particles. Therefore, by using them in copy toners, magnetic inks, and MR fluids, the properties can be fully exhibited.

[0030] (white powder) The composite particles of the seed particles and the cobalt ferrite particles can be whitened to form a white powder, or can be whitened and then provided with a colored layer to form a colored powder. The whitening can be performed by a known method, but it is preferable to use, for example, the whitening method patented by the applicant of the present application (Patent No. 4113045). This whitening method is a method for whitening powder by providing a titanium oxide film between the base particle and the metallic silver film. Specifically, the titanium oxide film is formed on the surface of the cobalt ferrite particle by hydrolysis of titanium alkoxide (e.g., International Publication No. 96 / 28269) or reaction from a titanium salt aqueous solution (e.g., JP-A-11-131102), and then the metallic silver film is formed by a known method such as electroless plating. By this method, a white powder having a titanium oxide film and a metallic silver film in this order on the surface of the composite particle of the seed particle and the cobalt ferrite particle of this embodiment can be produced, and as a result, the brightness L* of the composite particle of the seed particle and the cobalt ferrite particle can be improved to 75 or more. EXAMPLES

[0031] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples. The particle size distribution, average circularity, and magnetic properties of the composite particles of the seed particles and the cobalt ferrite particles produced were measured by the following methods.

[0032] (Particle size measurement) The particle size distribution of the composite particles of the seed particles and the cobalt ferrite particles was measured using a laser diffraction / scattering type particle size distribution measuring device (Microtrack Bell, model number "MT3300EXII"), and the particle size corresponding to the cumulative value of 50% based on the particle size distribution was determined as D 50 , and D, which is the particle size corresponding to 95% of the cumulative value based on the particle size distribution 95 was evaluated.

[0033] (SEM observation) The surfaces of the obtained composite particles were observed using a scanning electron microscope (manufactured by Hitachi High-Tech Corporation, model number "S-4800").

[0034] (Measurement of average circularity) The average circularity of the composite particles of seed particles and cobalt ferrite particles was evaluated by image analysis of SEM photographs (Mac-View Ver.4 software, manufactured by Mountec Co., Ltd.). For more than 100 composite particles per sample, the circularity was calculated as 4πS / L using the projected area S and perimeter L on the SEM photograph. 2 The average value was determined as the average circularity.

[0035] (Measurement of magnetic properties) The magnetic properties of the composite particles of seed particles and cobalt ferrite particles were evaluated using a vibrating sample magnetometer (VSM) (Tamagawa Seisakusho, model number "TM-VSM101483N7-MRO"). Hysteresis curves or demagnetization curves were obtained at a maximum magnetic field of 10,000 Oe, and the saturation magnetic moment, remanent magnetic moment, and coercive force were measured.

[0036] [Example 1] (Production of composite particles of seed particles and cobalt ferrite particles) (1) Preparation of raw material aqueous solution A raw material aqueous solution was prepared by dissolving 604.73 g of trisodium citrate dihydrate (C6H5Na3O7·2H2O), 95.38 g of cobalt(II) sulfate heptahydrate (CoSO4·7H2O), and 17.30 g of sodium nitrate (NaNO3) in 1,537.55 g of demineralized water, degassing with N2, and then dissolving 471.72 g of iron(II) sulfate heptahydrate (FeSO4·7H2O). (2) Preparation of ferrite precursor While continuing degassing with N2, a 48.5% aqueous solution of sodium hydroxide was added to the raw material aqueous solution to adjust the pH to 7.5, thereby preparing a ferrite precursor. (3) Preparation of magnetic particles by hydrothermal treatment Into an autoclave purged with N2, 50.00 g of iron (Fe) was placed as seed particles together with the ferrite precursor, and hydrothermal treatment was carried out at 200°C for 16 hours with stirring to obtain magnetic particles. (4) Washing of magnetic particles The magnetic particles were filtered and washed with demineralized water. (5) Drying of magnetic particles The washed magnetic particles were dried in air at 250° C. for 1 hour.

[0037] [Example 2] Magnetic particles were produced under the same conditions as in Example 1, except that in (3) Preparation of magnetic particles by hydrothermal treatment in Example 1, the amount of iron (Fe) was changed to 100.00 g.

[0038] [Example 3] In (3) Preparation of magnetic particles by hydrothermal treatment in Example 1, magnetic particles were produced under the same conditions as in Example 1, except that the amount of iron (Fe) was changed to 75.00 g and the hydrothermal treatment was changed to a two-stage treatment with the first stage being at 200°C for 12 hours and the second stage being at 220°C for 2 hours.

[0039] [Example 4] In (3) Preparation of magnetic particles by hydrothermal treatment in Example 1, magnetic particles were produced under the same conditions as in Example 1, except that the hydrothermal treatment was changed to a two-stage treatment, with the first stage being at 200°C for 4 hours and the second stage being at 240°C for 30 minutes.

[0040] [Example 5] Magnetic particles were produced under the same conditions as in Example 1, except that in (3) Preparation of magnetic particles by hydrothermal treatment in Example 1, the amount of iron (Fe) was changed to 25.00 g and the hydrothermal treatment was carried out at 190° C. for 40 hours.

[0041] [Example 6] Magnetic particles were produced under the same conditions as in Example 1, except that in (1) preparing the raw material aqueous solution in Example 1, the amount of trisodium citrate dihydrate (C6H5Na3O7 2H2O) was changed to 778.36 g, and in (3) preparing the magnetic particles by hydrothermal treatment, the 50.00 g of iron (Fe) seed particles was changed to 14.10 g of zinc ferrite, a type of spinel ferrite.

[0042] [Example 7] Magnetic particles were produced under the same conditions as in Example 1, except that in (3) Preparation of magnetic particles by hydrothermal treatment in Example 1, iron (Fe) as seed particles was changed to alnico, a type of iron-based alloy.

[0043] [Example 8] Magnetic particles were produced under the same conditions as in Example 1, except that in (3) Preparation of magnetic particles by hydrothermal treatment in Example 1, 50.00 g of iron (Fe) as seed particles was changed to 25.00 g of magnetite, a type of iron oxide.

[0044] [Example 9] Magnetic particles were produced under the same conditions as in Example 1, except that in (3) Preparation of magnetic particles by hydrothermal treatment, 50.00 g of iron (Fe) as seed particles was changed to 6.04 g of silica.

[0045] [Example 10] Magnetic particles were produced under the same conditions as in Example 1, except that in (1) preparation of the raw material aqueous solution in Example 1, 471.72 g of iron (II) sulfate heptahydrate (FeSO4·7H2O) as the ferrous salt was replaced with 337.29 g of iron (II) chloride tetrahydrate (FeCl2·4H2O), and in (3) preparation of the magnetic particles by hydrothermal treatment, the amount of iron (Fe) was changed to 14.10 g.

[0046] [Reference example 1] Magnetic particles were produced under the same conditions as in Example 1, except that sodium nitrate (NaNO3) was not added as an oxidizing agent in the preparation of the raw material aqueous solution in Example 1(1). [Reference example 2] Magnetic particles were produced under the same conditions as in Example 1, except that (1) in preparing the raw material aqueous solution, no sodium nitrate (NaNO3) was added as an oxidizing agent; and (3) in preparing the magnetic particles by hydrothermal treatment, the hydrothermal treatment was changed to a two-stage process, with the first stage being at 200°C for 12 hours and the second stage being at 220°C for 10 hours.

[0047] [Comparative Example 1] Magnetic particles were produced under the same conditions as in Example 1, except that in (3) Preparation of magnetic particles by hydrothermal treatment in Example 1, 50.00 g of iron (Fe) was replaced with 25.00 g of magnetite (Fe3O4), a type of iron oxide. The magnetite used in Comparative Example 1 had a non-spherical shape.

[0048] [Comparative Example 2] Magnetic particles were produced under the same conditions as in Example 1, except that in (3) Preparation of magnetic particles by hydrothermal treatment in Example 1, 50.00 g of iron (Fe) was replaced with 50.00 g of magnetite (Fe3O4), a type of iron oxide. The magnetite used in Comparative Example 2 was non-spherical in shape.

[0049] [Comparative Example 3] Magnetic particles were produced under the same conditions as in Example 1, except that in preparing the raw material aqueous solution (1) in Example 1, trisodium citrate dihydrate (C6H5Na3O7·2H2O) as a complexing agent and sodium nitrate (NaNO3) as an oxidizing agent were not used.

[0050] Various properties of the composite particles obtained in each of the Examples, Reference Examples, and Comparative Examples are summarized in Table 1. In addition, Fig. 1A, Fig. 1B to Fig. 15A, and Fig. 15B show SEM photographs of the composite particles and their seed particles in Examples 1 to 10, Reference Examples 1 and 2, and Comparative Examples 1 to 3.

[0051] [Table 1]

[0052] The reaction rates of Examples 1 to 3, Examples 5 to 10, Reference Example 1, Reference Example 2, Comparative Example 1, and Comparative Example 2 in the table were calculated according to the following formula A. The reaction rate of Example 4 was calculated according to formula B. The reaction rate of Comparative Example 3 could not be calculated because impurities were mixed into the reaction product. Formula A: (mass of powder actually obtained by hydrothermal treatment of ferrite precursor - amount of seed particles charged) / {charged raw material *2 Cobalt ferrite (Co) is obtained when all the iron and cobalt in the x Fe (3-x) O4) theoretical mass x 100 Formula B: {1-(mass concentration of iron and cobalt dissolved in the aqueous solution after hydrothermal treatment) / (theoretical mass concentration of iron and cobalt in the ferrite precursor before hydrothermal treatment)}×100 *2: The mass of iron and cobalt in the charged raw materials does not include the mass of iron and cobalt contained in the seed particles.

[0053] The composite particles of Example 1 had an average circularity of 0.81, a particle size corresponding to a cumulative value of 50% based on the particle size distribution of 5.58 μm, and a particle size corresponding to a cumulative value of 95% based on the particle size distribution of 9.81 μm. As shown in FIG. 1A, the composite particles of Example 1 had a rounded shape.

[0054] The composite particles of Example 2 had an average circularity of 0.79, a particle size corresponding to a cumulative value of 50% based on the particle size distribution of 4.63 μm, and a particle size corresponding to a cumulative value of 95% based on the particle size distribution of 8.10 μm. As shown in FIG. 2A, the composite particles of Example 2 had a rounded shape.

[0055] The composite particles of Example 3, which were heat-treated in two stages with a first temperature reached at 200°C and a second temperature reached at 220°C, had an average circularity of 0.80, a particle diameter corresponding to 50% of the cumulative value based on the particle size distribution of 5.85 μm, and a particle diameter corresponding to 95% of the cumulative value based on the particle size distribution of 11.32 μm. As shown in FIG. 3A, the composite particles of Example 3 had a rounded shape.

[0056] The composite particles of Example 4, which were heat-treated in two stages with a first temperature reached at 200°C and a second temperature reached at 240°C, had an average circularity of 0.76, a particle diameter corresponding to 50% of the cumulative value based on the particle size distribution of 6.23 μm, and a particle diameter corresponding to 95% of the cumulative value based on the particle size distribution of 11.89 μm. As shown in FIG. 4A, the composite particles of Example 4 had a rounded shape.

[0057] The composite particles of Example 5 that were heat-treated at 190°C had an average circularity of 0.80, a particle diameter corresponding to 50% cumulative value based on the particle size distribution of 5.17 μm, and a particle diameter corresponding to 95% cumulative value based on the particle size distribution of 9.38 μm. As shown in FIG. 5A, the composite particles of Example 5 had a rounded shape.

[0058] The composite particles of Example 6, in which zinc ferrite, a type of spinel ferrite, was used as the seed particles, had an average circularity of 0.92, a particle diameter corresponding to a cumulative value of 50% based on the particle size distribution of 29.73 μm, and a particle diameter corresponding to a cumulative value of 95% based on the particle size distribution of 47.31 μm. As shown in FIG. 6A, the composite particles of Example 6 had a rounded shape.

[0059] The composite particles of Example 7, which used alnico, an iron-based alloy, as seed particles, had an average circularity of 0.86, a particle size corresponding to 50% cumulative value based on particle size distribution of 11.27 μm, and a particle size corresponding to 95% cumulative value based on particle size distribution of 24.41 μm. As shown in FIG. 7A, the composite particles of Example 7 had a rounded shape.

[0060] The composite particles of Example 8, which used approximately spherical iron oxide as the seed particles, had an average circularity of 0.80, a particle diameter corresponding to 50% cumulative value based on the particle size distribution of 23.16 μm, and a particle diameter corresponding to 95% cumulative value based on the particle size distribution of 38.43 μm. As shown in FIG. 8A, the composite particles of Example 8 had a rounded shape.

[0061] The composite particles of Example 9, in which silica was used as the seed particles, had an average circularity of 0.70, a particle diameter corresponding to 50% of the cumulative value based on the particle size distribution of 9.06 μm, and a particle diameter corresponding to 95% of the cumulative value based on the particle size distribution of 15.47 μm. As shown in FIG. 9A, the composite particles of Example 9 had a rounded shape.

[0062] The composite particles of Example 10, in which iron (II) chloride tetrahydrate was added as the divalent iron salt and cobalt (II) chloride hexahydrate was added as the cobalt salt in preparing the raw aqueous solution, had an average circularity of 0.88, a particle diameter corresponding to 50% of the cumulative value based on the particle size distribution of 14.21 μm, and a particle diameter corresponding to 95% of the cumulative value based on the particle size distribution of 25.58 μm. As shown in FIG. 10A, the composite particles of Example 10 had a rounded shape.

[0063] The composite particles of Comparative Example 1, in which non-spherical magnetite was used as the seed particles, had an average circularity of 0.69, a particle diameter corresponding to 50% of the cumulative value based on the particle diameter distribution of 5.26 μm, and a particle diameter corresponding to 95% of the cumulative value based on the particle diameter distribution of 9.46 μm. As shown in FIG. 13A, the composite particles of Comparative Example 1 were not rounded and had irregular shapes.

[0064] The composite particles of Comparative Example 2, in which non-spherical magnetite was used as the seed particles, had an average circularity of 0.63, a particle diameter corresponding to 50% of the cumulative value based on the particle diameter distribution of 3.96 μm, and a particle diameter corresponding to 95% of the cumulative value based on the particle diameter distribution of 6.98 μm. As shown in FIG. 14A, the composite particles of Comparative Example 2 were not rounded and had irregular shapes.

[0065] The composite particles of Comparative Example 3, which did not contain a complexing agent or an oxidizing agent, had an average circularity of 0.53, a particle diameter corresponding to 50% cumulative value based on the particle diameter distribution of 4.48 μm, and a particle diameter corresponding to 95% cumulative value based on the particle diameter distribution of 19.57 μm. In addition, as shown in the white frame in FIG. 15A, the reaction product of Comparative Example 3 contained impurities. As shown in FIG. 15A, the composite particles of Comparative Example 3 were not rounded and had irregular shapes.

[0066] The results in Table 1 show that in all of Examples 1 to 10, by adding seed particles to a ferrite precursor stabilized with a complexing agent and then heat-treating it, composite particles of seed particles and cobalt ferrite particles are formed which have an average circularity in the range of 0.7 to 1.0, a rounded shape, and specific magnetic properties.

[0067] In Example 1, the temperature was 200°C and the holding time was 16 hours, whereas in Example 3, which was heat-treated at 200°C as the first stage and 220°C as the second stage, the total holding time was 14 hours, and in Example 4, which was heat-treated at 200°C as the first stage and 240°C as the second stage, the total holding time was 4 hours and 30 minutes. It was shown that the total heat treatment time was shortened when heat treatment was performed in two stages.

[0068] The composite particles of Example 5 had an average circularity in the range of 0.7 to 1.0, a rounded shape, and specific magnetic properties. From the results of Example 5, it was found that even when the heating temperature was 190° C., composite particles of seed particles and cobalt ferrite particles could be obtained that had an average circularity of 0.7 to 1.0, a rounded shape, and specific magnetic properties.

[0069] The composite particles of Example 6 had an average circularity in the range of 0.7 to 1.0, a rounded shape, and specific magnetic properties. The particle diameter corresponding to 50% of the cumulative value based on the particle size distribution of Example 6 was 29.73 μm, and the particle diameter corresponding to 95% of the cumulative value was 47.31 μm, so it was found that the method for producing composite particles of seed particles and cobalt ferrite particles can provide particles with a particle diameter of 30 μm or less corresponding to 50% of the cumulative value based on the particle size distribution and particles with a particle diameter of 50 μm or less corresponding to 95% of the cumulative value.

[0070] The composite particles of Examples 7 to 9 had an average circularity in the range of 0.7 to 1.0, a rounded shape, and specific magnetic properties. From the results of Examples 1 and 6 to 9, it was found that when iron, iron-based alloy, iron oxide, spinel ferrite, or silica was used as the seed particles, composite particles of seed particles and cobalt ferrite particles having an average circularity of 0.7 to 1.0, a rounded shape, and specific magnetic properties were obtained.

[0071] The composite particles of Example 10 had an average circularity in the range of 0.7 to 1.0, a rounded shape, and specific magnetic properties. From the results of Example 10, it was found that even if iron chloride (II) is used as the divalent iron salt and cobalt chloride (II) is used as the cobalt salt in the preparation process of the ferrite precursor, composite particles of seed particles and cobalt ferrite particles having an average circularity in the range of 0.7 to 1.0, a rounded shape, and specific magnetic properties can be obtained.

[0072] 1B to 10B, the shapes of the iron (Fe), zinc ferrite which is a type of spinel ferrite, alnico which is a type of iron-based alloy, magnetite which is a type of iron oxide, and silica used as seed particles in Examples 1 to 10 were spherical or nearly spherical. On the other hand, as shown in Figs. 13B and 14B, the shape of the magnetite used as seed particles in Comparative Examples 1 and 2 was not spherical or nearly spherical. Comparing Examples 1 to 10 with Comparative Examples 1 and 2, it was found that by using spherical or nearly spherical seed particles, composite particles of seed particles and cobalt ferrite particles having an average circularity in the range of 0.7 to 1.0, a rounded shape, and specific magnetic properties can be obtained.

[0073] The cross-sectional structure of the obtained composite particles was confirmed by observation using a transmission electron microscope (TEM). 16A and 16B are cross-sectional conceptual diagrams of the composite particles of Example 1 as a representative example with seed particles. It was confirmed that the obtained composite particles were core-shell type composite particles A as shown in Fig. 16A, or composite particles A were aggregated together to form islands-in-the-sea type composite particles B (B-1 to B-4) having a plurality of seed particles as shown in Fig. 16B. In this specification, when the term "particle diameter" is used simply, it refers to the diameter of the outermost shell of a composite particle, as shown by arrow a in FIG. 16A and arrow b in FIG. 16B.

[0074] The results of Reference Example 1 in Table 1 show that composite particles of seed particles and cobalt ferrite particles can be obtained even without adding an oxidizing agent. The reaction rate of Reference Example 1 was 8.6%, which was lower than the reaction rate of Example 1, 79.9%.

[0075] The test conditions for Reference Example 1 were the same as those for Example 1, except that sodium nitrate (NaNO3) was not added as an oxidizing agent in the preparation of the raw aqueous solution (1) of Example 1. From this, it was found from a comparison between Example 1 and Reference Example 1 that the reaction rate was significantly improved by adding an oxidizing agent.

[0076] The composite particles of Reference Example 2 had an average circularity in the range of 0.7 to 1.0, a rounded shape, and specific magnetic properties. The reaction rate of Reference Example 2 was 63.5%, which was higher than the reaction rate of Reference Example 1. The test conditions for Reference Example 2 were the same as those for Example 1, except that (1) in preparing the raw material aqueous solution, no sodium nitrate (NaNO3) was added as an oxidizing agent; and (3) in preparing the magnetic particles by hydrothermal treatment, the hydrothermal treatment was changed to a two-stage process, with the first stage being at 200°C for 12 hours and the second stage being at 220°C for 10 hours. Comparing Reference Example 1 with Reference Example 2, it was found that even when an oxidizing agent is not added, by increasing the heat treatment temperature and conducting the heat treatment in two stages, the average circularity and reaction rate of the composite particles are improved, and composite particles of seed particles and cobalt ferrite particles having an average circularity in the range of 0.7 to 1.0, a rounded shape, and specific magnetic properties can be obtained.

[0077] [Example 11] (Whitening of cobalt ferrite particles) A yellow transparent peroxotitanic acid solution was prepared by mixing 4.49g of tetra-i-propoxytitanium titanium solution (27.9-28.5% asTi), 14.40g of ammonia water, and 12.50g of hydrogen peroxide water in 23.30g of deionized water. 4.95g of anhydrous boric acid, 5.96g of potassium chloride, and 1.28g of sodium hydroxide were dissolved in 267.81g of deionized water, and 122.50g of the composite particles of Example 1 were suspended. The peroxotitanic acid solution was added dropwise while stirring the suspension, and then the suspension was dried to obtain a titanium oxide-coated powder. A reducing solution was prepared by dissolving 9.08g of glucose, 1.01g of tartaric acid, 8.15g of ethanol, 0.92g of n-propanol, and 0.47g of i-propanol in 100.38g of deionized water. A silver ammine complex solution was prepared by mixing 5.00g of sodium hydroxide, 7.00g of silver nitrate, and 12.00g of ammonia water with 360.00g of deionized water, and 29.70g of titanium oxide-coated powder was suspended in this. The reducing solution was mixed into the suspension while irradiating it with ultrasound, and the suspension was dried to obtain a silver-film-coated powder. The resulting white powder had a brightness L* of 79.73. [Industrial Applicability]

[0078] The composite particles of seed particles and cobalt ferrite particles obtained by the production method of the present invention have a rounded shape and a uniform particle size, and are therefore expected to be used as copy toners, magnetic inks, and MR fluids.

Claims

1. preparing a ferrite precursor by stabilizing a divalent iron salt and a cobalt salt in an aqueous solution with a complexing agent; adding spherical or nearly spherical seed particles to the ferrite precursor; The method for producing composite particles of seed particles and cobalt ferrite particles further comprises a step of heat-treating the ferrite precursor.

2. 2. The method for producing composite particles of seed particles and cobalt ferrite particles according to claim 1, wherein the heat treatment is carried out in a pressure vessel under hydrothermal conditions in a temperature range of 130° C. to 260° C.

3. 3. The method for producing composite particles of seed particles and cobalt ferrite particles according to claim 2, wherein the heat treatment is carried out in a pressure vessel under hydrothermal conditions in a temperature range of 190° C. to 240° C.

4. 4. The method for producing composite particles of seed particles and cobalt ferrite particles according to claim 2, wherein the time for the heat treatment step is 1 to 50 hours.

5. The heat treatment includes heating to a temperature range of 190° C. to 210° C. and maintaining the first reached temperature, The method for producing composite particles of seed particles and cobalt ferrite particles according to claim 3, further comprising heating the mixture to a temperature range of 210° C. to 240° C. and maintaining the mixture at the second reached temperature under hydrothermal conditions.

6. The method for producing composite particles of seed particles and cobalt ferrite particles according to claim 5, wherein the first attained temperature is maintained for 1 to 14 hours.

7. The method for producing composite particles of seed particles and cobalt ferrite particles according to claim 5 or 6, wherein the second attained temperature is maintained for 0.5 to 12 hours.

8. 4. The method for producing composite particles of seed particles and cobalt ferrite particles according to claim 2 or 3, wherein at least one selected from the group consisting of iron, an iron-based alloy, iron oxide, spinel ferrite, and silica is used as the seed particles.

9. 4. The method for producing composite particles of seed particles and cobalt ferrite particles according to claim 2, wherein the divalent iron salt and the cobalt salt are iron (II) sulfate and cobalt (II) sulfate.

10. 4. The method for producing composite particles of seed particles and cobalt ferrite particles according to claim 2, wherein the divalent iron salt and the cobalt salt are iron (II) chloride and cobalt (II) chloride.

11. 4. The method for producing composite particles of seed particles and cobalt ferrite particles according to claim 2 or 3, wherein the complexing agent is one selected from the group consisting of citrate, nitrilotriacetate, and malate.

12. 4. The method for producing composite particles of seed particles and cobalt ferrite particles according to claim 2, wherein the heat treatment step is carried out in the presence of an oxidizing agent in addition to a complexing agent.

13. The method for producing composite particles of seed particles and cobalt ferrite particles according to claim 12, wherein the oxidizing agent is a nitrate.

14. 4. The method for producing composite particles of seed particles and cobalt ferrite particles according to claim 2, further comprising adding a trivalent iron salt to the aqueous solution containing the ferrite precursor.

15. 4. The method for producing composite particles of seed particles and cobalt ferrite particles according to claim 2, further comprising adding a pH buffer to the aqueous solution containing the ferrite precursor.

16. 4. The method for producing composite particles of seed particles and cobalt ferrite particles according to claim 2 or 3, further comprising the steps of: injecting an alkaline aqueous solution or a ferrite precursor into the pressure vessel during or after the step of carrying out the heat treatment; and carrying out a further heat treatment.

17. It has a rounded shape with an average circularity of 0.7 to 1.0, A particle size corresponding to a cumulative 50% value based on the particle size distribution is 1 to 30 μm; The particle size corresponding to 95% cumulative value based on the particle size distribution is 5 to 50 μm. Composite particles of seed particles and cobalt ferrite particles.

18. 18. The composite particle of seed particles and cobalt ferrite particles according to claim 17, which has a remanent magnetic moment of 10 emu / g or more and a coercive force of 100 to 1000 Oe.

19. A toner for copying comprising composite particles of the seed particles according to claim 18 and cobalt ferrite particles.

20. A magnetic ink comprising composite particles of the seed particles according to claim 18 and cobalt ferrite particles.

21. 20. An MR fluid comprising composite particles of the seed particles according to claim 18 and cobalt ferrite particles.

22. 20. A white powder comprising a composite particle of the seed particle and the cobalt ferrite particle according to claim 18, and a titanium oxide film and a metallic silver film formed in this order on the surface of the composite particle.

23. The white powder according to claim 22, having a lightness L* of 75 or more.

Citation Information

Patent Citations

  • Novel ester

    JP1980004399A

  • Car door

    JP1985047722A

  • Position display apparatus for vehicle

    JP1991024412A

  • Production of (Zn, mn, ni) ferrite particles well-ordered in grain diameters

    JP1993275224A

  • Method for producing single-crystal cobalt ferrite fine particles

    JP4138344B2